PENGARUH COMMUNICATION, WORK DISCIPLINE DAN WORK LIFE BALANCE TERHADAP KINERJA KARYAWAN YANG DIMEDIASI OLEH MOTIVASI KERJA PADA PT X BOYOLALI - Dwi Eko Prasetyo; Nur Achmad (POLITEKNIK LP3I JAKARTA, 2025)
The objective of this research is to examine the extent to which communication, work discipline, and work-life balance influence employee performance, with work motivation functioning as a mediating variable. The target population comprises employees of PT X located in Boyolali. A purposive sampling method was employed, resulting in a total sample of 130 participants. Data collection was conducted through a structured questionnaire utilizing a Likert scale to measure responses. The analytical approach adopted in this study was Partial Least Squares (PLS), executed using the SMARTPLS 4.0 software. The PLS-SEM method involves the evaluation of both the measurement model (outer model) and the structural model (inner model). Empirical findings indicate that neither communication nor work discipline exert a statistically significant influence on employee performance, whereas work-life balance demonstrates a positive impact. Furthermore, communication, work discipline, and work-life balance are all found to significantly affect work motivation. While communication does not significantly influence employee performance through the mediating role of motivation, work motivation is found to mediate the relationship between both work discipline and work-life balance with employee performance.